Profiles of attitudes toward inclusive education among Chinese in-service teachers: their relationships with demographic factors and organizational commitment - Deng, Yuhao; Yuan, Wei; Zhang, Li-fang; Xie, Zhengli (Frontiers in Psychology, 2024)
Introduction The increased diversity of students (e.g., students with special educational needs) has presented teachers with unprecedented challenges. Teachers’ attitudes toward inclusive education play a crucial role in teachers’ organizational well-being. However, existing studies mostly explored attitudes toward inclusive education based on a variable-centered approach. This study used a person-centered approach to identify teachers’ attitude profile membership and explored the relationships of attitude profiles with demographic factors (i.e., gender, years of teaching experience, subject taught, and in-service training) and organizational commitment. Methods Nine hundred and seventy-two in-service teachers from forty-nine inclusive education schools in Beijing responded to the Revised Multidimensional Attitudes toward Inclusive Education Scale and the Organizational Commitment Inventory. Latent profile analyses, multinomial logistic regression, and univariate analysis of variance were used to analyze data. Results and discussion The results revealed four attitude profiles: involuntary participation, behavior avoidance, neutral, and proactive involvement. Years of teaching experience and in-service training were significant predictors of teachers’ latent profile membership. Teachers belonging to the involuntary participation profile showed the highest levels of maladaptive commitments to inclusive education schools. Teachers belonging to the proactive involvement and the behavior avoidance profiles showed higher levels of adaptive commitments. However, teachers belonging to the neutral profile had the lowest levels of adaptive commitments. The theoretical contributions, practical implications, and limitations are discussed.